An audio encryption using transposition method - Ahmad Jawahir; Haviluddin Haviluddin (Universitas Ahmad Dahlan, 2015)
Encryption is a technique to secure sounds data from attackers. In this study, transposition technique that corresponds to a WAV file extension is used. The performance of the transposition technique is measured using the mean square error (MSE). In the test, the value of MSE of the original and encrypted audio files were compared; the original and decrypted audio files used the correct password is ‘SEMBILAN’ and the incorrect password is ‘DELAPAN’. The experimental results showed that the original and encrypted audio files, and the original and decrypted audio files used the correct password that has a value of MSE = 0, and with the incorrect one with a value of MSE 0.00000428 or ≠ 0. In other words, the transposition technique is able to ensure the security of audio data files.